The Influence of Job Satisfaction and Reward Systems on Turnover Intention - Firmansyah, Muhamad Endra; Isnanto, Samto Hadi (Dinasti Publisher, 2025)
High turnover intention poses a significant challenge for many organizations, particularly in retaining skilled employees. This study aims to analyze the influence of job satisfaction and reward systems on turnover intention through a literature review. The research employs a systematic literature review method by examining previous studies that discuss the relationship between job satisfaction, reward systems, and employees' intention to leave an organization. The findings indicate that job satisfaction plays a crucial role in reducing turnover intention. Factors such as a supportive work environment, good relationships with colleagues and supervisors, and career development opportunities contribute to increased job satisfaction. Furthermore, a fair and competitive reward system, both financial and non-financial, is proven to be effective in enhancing employee retention. Conversely, dissatisfaction with the reward system is a primary driver for employees to seek alternative job opportunities. Therefore, organizations must develop appropriate strategies to manage job satisfaction and reward systems to minimize turnover intention and enhance employee loyalty.